Stres dan Pengetahuan Mempengaruhi Efikasi Diri Ibu Hamil dalam Pencegahan Preeklampsi - Shinta Wahyusari; Rif'atul Fani (Poltekkes Kemenkes Jakarta III, 2023)
Self-efficacy is very important to determine pregnant women's confidence in taking preeclampsia prevention measures. Pregnant women with high self-efficacy will actively participate in planning care during pregnancy to achieve healthy conditions for the mother and baby, whereas poor self-efficacy results in feelings of frustration and anger during pregnancy. The aim of this study was to determine the relationship between knowledge and stress and the self-efficacy of pregnant women in preventing preeclampsia. This research uses a correlational analytical design with a cross sectional approach. The sample in this study was 60 pregnant women who were at risk of preeclampsia. Samples were selected using purposive sampling technique in accordance with previously determined inclusion and exclusion criteria. Data collection uses a questionnaire. Data analysis used the Spearman correlation test. The results of the analysis show that there is a relationship between knowledge (p: 0.015; r: 0.311) and stress (p: 0.048; r: -0.256) with the self-efficacy of pregnant women in preventing preeclampsia. Based on these results, efforts need to be made to increase knowledge and reduce stress in pregnant women through education and stress management activities so that they can increase the self-efficacy of pregnant women.